Cultural factors promoting coping among Tibetan refugees: a qualitative investigation - Hussain, Dilwar (Mental health, religion & culture, 2011)
This study is an attempt to understand the role of cultural resources in promoting coping among Tibetan refugees. Tibetan refugee communities have adapted well and managed to preserve their cultural identity in exile and have been cited as models of successful coping with refugee life. Tibet is renowned for its rich culture and traditions. The unique feature of this culture is the devotion towards Buddhism which has exerted a strong influence in almost every aspect of their life and culture. This study is a qualitative investigation of 12 Tibetan refugees coming from diverse background (students, businessmen, activists, and ex-prisoners). Interpretive phenomenological analysis was used to analyse the narratives of case studies in order to explore various cultural factors promoting healthy coping. Major themes related to the cultural resources promoting healthy coping included - protective hand of Dalai Lama and other Lamas, Buddhist philosophy and practices, community bonding and support, and historical exemplars of strength and resiliency.